2020
DOI: 10.4236/cm.2020.114008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of TCM Herbs on Mitochondrial Functions: The Linkage between Qi and Mitochondria

Abstract: The linkage between Qi and mitochondria was investigated by exploring the effect of Traditional Chinese Medicine (TCM) Qi-invigorating herbs on mitochondrial function at the biochemical and molecular levels. Three Chinese herbs (Astragali radix, Herba cistanche, Panax ginseng) were used to treat cultured mouse kidney cells and the generation of adenosine triphosphate (ATP) was measured. The Qi-invigorating herb, Astragali radix, was selected for further study using additional biological and molecular parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Cell growth depends on the comprehensive effects of biochemical and molecular processes that synthesize its various components inside the cell. In our previous experimental results, it was found that low dose of AR increased the content of ATP and GSH in cells [15]. ATP is the carrier of energy released by cells during respiration and directly provides energy for various life activities.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Cell growth depends on the comprehensive effects of biochemical and molecular processes that synthesize its various components inside the cell. In our previous experimental results, it was found that low dose of AR increased the content of ATP and GSH in cells [15]. ATP is the carrier of energy released by cells during respiration and directly provides energy for various life activities.…”
Section: Discussionmentioning
confidence: 89%
“…The transcription of E3 ligase proteins process of cell apoptosis [27]. High concentration of AR reduces the production of ATP and lowers the membrane potential of mitochondria [15]. Excessive mitochondrial fission can cause mitochondrial ROS overload and inhibit the production of mitochondrial ATP [28].…”
Section: Discussionmentioning
confidence: 99%
“…The cellular component category of the GO analysis revealed unique compounds related to mitochondria, which play a crucial role in cellular energy metabolism for ATP production [ 76 ]. Previous research has found that QIHs enhance mitochondrial ATP production ability [ 6 , 77 ], levels of ATP, adenylate energy charge, and total adenylate pool [ 1 ]. In the present study, the KEGG and GO analyses also revealed unique compounds related to neuron composition that are involved in neuroactive ligand–receptor interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Qi-invigorating herbs (QIHs) are a group of herbs that invigorate healthy Qi and that are used to improve the symptoms of Qi deficiency syndrome [ 2 ]. Recent studies have attempted to demonstrate the effects of various QIHs on mitochondria, the cellular “powerhouses,” to elucidate their energy-boosting effect [ 5 , 6 ]. Other studies have demonstrated the role of QIHs in fighting fatigue [ 7 ] and as antioxidants and immunostimulants [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The decrease of mitochondrial membrane potential can cause a series of biochemical changes in the mitochondrial membrane, which is an early event in the process of cell apoptosis [27]. High concentration of AR reduces the production of ATP and lowers the membrane potential of mitochondria [15]. Excessive mitochondrial ssion can cause mitochondrial ROS overload and inhibit the production of mitochondrial ATP [28].…”
Section: Discussionmentioning
confidence: 99%